Hydrolysis of Soybean By-Products to Prepare Reducing Sugar in Ionic Liquids - Hu1, X.M.; Zhang2, B.X.; Dong1, S.J.; Zhao1, Y.; Gao2, Y.F. (Asian Journal of Chemistry, 2014)
An efficient approach for preparation of reducing sugar from soybean hulls and soybean dregs in a series of ionic liquids was studied. The ionic liquids have excellent dissolved and catalytic ability. High yield was obtained with the use of 1,4-bis(3-methylimidazolium)butane hydrogen sulfate ([MIM]2C4[HSO4]2) and pretreatment with 1-allyl-3-methylimidazolium chloride [AMIM]Cl. The effects of several critical factors such as reaction temperature, reaction time and the amount of water and ionic liquid were investigated. At the optimum reaction conditions, the yield of reducing sugar from soybean hulls was up to 68.86 and 119.69 mg from 0.25 g soybean hulls and soybean dregs, respectively.